A narrative review of the synthesis, characterization, and applications of iron oxide nanoparticles - Joseph Ekhebume Ogbezode; Ucheckukwu Stella Ezealigo; Abdulhakeem Bello; Vitalis Chioh Anye; Azikiwe Peter Onwualu (Discover Nano, 2023)
Abstract The significance of green synthesized nanomaterials with a uniform shape, reduced sizes, superior mechanical capabilities, phase microstructure, magnetic behavior, and superior performance cannot be overemphasized. Iron oxide nanoparticles (IONPs) are found within the size range of 1–100 nm in nanomaterials and have a diverse range of applications in fields such as biomedicine, wastewater purification, and environmental remediation. Nevertheless, the understanding of their fundamental material composition, chemical reactions, toxicological properties, and research methodologies is constrained and extensively elucidated during their practical implementation. The importance of producing IONPs using advanced nanofabrication techniques that exhibit strong potential for disease therapy, microbial pathogen control, and elimination of cancer cells is underscored by the adoption of the green synthesis approach. These IONPs can serve as viable alternatives for soil remediation and the elimination of environmental contaminants. Therefore, this paper presents a comprehensive analysis of the research conducted on different types of IONPs and IONP composite-based materials. It examines the synthesis methods and characterization techniques employed in these studies and also addresses the obstacles encountered in prior investigations with comparable objectives. A green engineering strategy was proposed for the synthesis, characterization, and application of IONPs and their composites with reduced environmental impact. Additionally, the influence of their phase structure, magnetic properties, biocompatibility, toxicity, milling time, nanoparticle size, and shape was also discussed. The study proposes the use of biological and physicochemical methods as a more viable alternative nanofabrication strategy that can mitigate the limitations imposed by the conventional methods of IONP synthesis.